Chords and melodies for the beginning pianist, second level. - McGinley, Ed. (East Stroudsburg, Pennsylvania Shawnee Press, 1949)
Twenty Questions -- Melody Chords om the First level -- Melody Chords for the Right Hand -- Two New Chords...F# and B -- Motion of Four --The White Thumb Chords -- Tenths Played with Both Hands -- Summary of Chords and Motion -- Are You Curious -- Treble Clef and Bass Clef -- Note Values -- Dotted Notes -- Triplets -- Rests -- Melodies in Swing -- Key Signatures -- Time Signatures -- Exam Day -- Devices for Varying Tenths -- Answers to Quiz Questions.
Keywords: Piano -- Studies and exercises; Piano -- Instruction and study; Piano -- Methods